Evaluation of Root Canal Morphology and Root Apex Anatomy of Mandibular Premolars in an Iranian Population: an ex-vivo study - Naseri, Mandana; Mozayeni, Mohammad Ali; Adelkhani, Nahid; Gohari, Atefeh (Journal of Dental School, 2019)
Objectives Adequate knowledge about canal anatomy is necessary for clinicians to prevent any damage to the periodontium. The aim of this study was to evaluate the canal and apical complexities of the mandibular first and second premolars in an Iranian population. Methods One-hundred mandibular first (n=50) and second (n=50) premolars were collected. After access cavity preparation, 2% methylene blue was injected into the canals, and they were sealed with Coltosol and nail varnish. Next, demineralization and clearing with 5% nitric acid and methyl salicylate were performed. Apical morphology including the presence of accessory canals, apical delta, anastomoses and canal configurations was evaluated under a stereomicroscope at x16 magnification. Descriptive statistics (including tables, central tendency and dispersion tests) were used for data analysis. Results The most prevalent form of canal type was Vertucci’s type I in first and second premolars. The mean distance between the apical foramen and anatomic apex, apical foramen and apical constriction, and apical constriction and anatomic apex was 0.3, 0.6 and 0.9 mm, respectively for the first premolars. These values were 0.3, 0.5 and 0.8 mm, respectively for the second premolars. Conclusion Although most mandibular premolars have one canal, using appropriate cleaning methods is imperative because of high prevalence of accessory canals, anastomoses and apical deltas. First premolars pose more challenges in this respect